2018
DOI: 10.1007/s10555-018-9736-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of apoptotic caspases in tumor repopulation, epigenetic reprogramming, carcinogenesis, and beyond

Abstract: Apoptotic caspases have long been studied for their roles in programmed cell death and tumor suppression. With recent discoveries, however, it is becoming apparent these cell death executioners are involved in additional biological pathways beyond killing cells. In some cases, apoptotic cells secrete growth signals to stimulate proliferation of neighboring cells. This pathway functions to regenerate tissues in multiple organisms, but it also poses problems in tumor resistance to chemo- and radiotherapy. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 103 publications
1
54
0
Order By: Relevance
“…For example, it was suggested that expression patterns indicative of high apoptosis responsiveness may correlate with poor outcome if dormant, stem-like cancer cells that may reside within tumour tissues re-populate tumours and promote further spread and progression of the disease after the bulk population of cells has been eliminated by apoptosisinducing therapy 42,43 . In line with this, apoptotic cell loss can drive the proliferation of surrounding cells, for example, through caspase-dependent prostaglandin signalling and secretion of other proliferation stimulating factors from dying cells 60,61 . These signalling processes indeed might be of relevance in melanoma treatment responsiveness and disease relapse 62 .…”
Section: Discussionmentioning
confidence: 90%
“…For example, it was suggested that expression patterns indicative of high apoptosis responsiveness may correlate with poor outcome if dormant, stem-like cancer cells that may reside within tumour tissues re-populate tumours and promote further spread and progression of the disease after the bulk population of cells has been eliminated by apoptosisinducing therapy 42,43 . In line with this, apoptotic cell loss can drive the proliferation of surrounding cells, for example, through caspase-dependent prostaglandin signalling and secretion of other proliferation stimulating factors from dying cells 60,61 . These signalling processes indeed might be of relevance in melanoma treatment responsiveness and disease relapse 62 .…”
Section: Discussionmentioning
confidence: 90%
“…Genotoxic anticancer agents activate the mitochondrial or intrinsic pathway of apoptosis (reviewed in [106][107][108]). The process is initiated by mitochondrial outer membrane permeabilization (MOMP), resulting in the release of cytochrome c and other intermembrane space proteins.…”
Section: Therapy-induced Cancer Cell Apoptosis and Disease Relapsementioning
confidence: 99%
“…Although MOMP and caspase-3 activation continue to be used as molecular markers of cell death, relatively recent studies demonstrated that, under some circumstances, instead of functioning as an apoptosis executioner, active caspase-3 plays an important role in carcinogenesis, metastasis, and therapy resistance (reviewed in [107,[112][113][114][115][116][117][118][119][120]). Caspase-3 can stimulate tumor cell growth through various routes.…”
Section: Role Of Caspase-3 In Tumor Repopulationmentioning
confidence: 99%
See 2 more Smart Citations